Once Again About the Need to Reform the Legislationon Administrative Responsibility - Y. P. Solovey (Сибирское юридическое обозрение, 2019)
The article substantiates the insolvency of the position of Professor Yuri N. Starilov, declared at the All-Russian scientific-practical conference “Actual problems of administrative responsibility” (Omsk Law Academy, May 24, 2019) and reflected in his commentary on the concept of the new Code of the Russian Federation on Administrative Offenses (approved on June 5, 2019 at a meeting with the Chairman of the Government of the Russian Federation), on the prematureness of the reform of the Russian legislation on administrative offenses. The need for reform, in the opinion of the Author of the article, is due to the fact that the current legislation on administrative responsibility (the quality of which left much to be desired at the time of its adoption), which continues to steadily deteriorate as many laws are introduced into this legislation, from the instrument of maintaining law and order and ensuring of proper state management by the efforts of state power has become an instrument of excessive administrative pressure of the state on society, its institution and the individual person, the active use of which causes irritation and discontent among citizens, creates tension in their relations with the authorities. Judging by some of the areas of reform of the Code of the Russian Federation on Administrative Offenses defined by the concept, its developers are aware of the true reasons for the reform, which, for wellknown reasons, were not reflected in the document. In this regard, there is a certain chance that the new Code of the Russian Federation on Administrative Offenses will prove to be better than its predecessor, will be more consistent with the principles of a legal, democratic state, enshrined in the Constitution of the Russian Federation.